Biomechanical, coordinative, and physiological responses to a time-to-exhaustion protocol at two submaximal intensities in swimming - Marcos Franken; Pedro Figueiredo; Ricardo Peterson Silveira; Flávio Antônio de Souza Castro (Revista da Educação Física)
The aim of this study was to compare biomechanical, coordinative and physiological parameters in the front crawl, during interval training series performed in two submaximal intensities until exhaustion. Eleven swimmers, mean age of 21.0 ± 7.3 years, performed two sets of interval training with repetitions of 400 m (40 s of passive rest) at 90% (s90) and 95% (s95) of the 400 m front crawl mean speed (s400), which was previously determined during a maximum 400 m test. The results were: (i) increase in the stroke frequency and decrease in the stroke length between the trials and between the initial and final repetitions in the s90 and s95 series; (ii) index of coordination and propulsive time increased between the initial and final trials in the s95 series; (iii) the absolute and relative durations of the pull phase increased between the initial and final repetitions of the s95 series; (iv) perceived exertion, lactate concentration and heart rate increased between the initial and final repetitions in s90 and s95. To maintain speed in the s90 and s95 series of s400 leads to changes in the motor organization of the stroke in the front crawl.